Screening of tomato varieties against tomato fruit borer and associated plant characters - Amin, MR; Chakma, A; Alam, MZ; Hossain, MM; Ge, F (SAARC Journal of Agriculture, 2017)
Ten tomato varieties were evaluated to find out their level of resistance against tomato fruit borer Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) under field conditions. The abundance of fruit borer larvae and their infestation, plant morphological characters, nitrogen content, yield and seed germination of the varieties were studied. The varieties differed in their leaf thickness, trichome density, rind thickness and nitrogen content. The fruit borer larval abundance and fruit infestation among the varieties varied significantly. Five varieties namely BARI Tomato-1, BARI Tomato-4, BARI Tomato-10, BARI Tomato-11 and BARI Tomato-15 were least infested by fruit borer (3.6 to 10.0%) and had significantly lower abundance of larvae (0.3 to 0.7 plant-1), and the varieties were classified as resistant. The yield reduction and seed germination of these varieties ranged from 3.9 to 7.9% and 76.7 to 90.7%, respectively. Four varieties namely BARI Tomato-2, BARI Tomato-5, BARI Tomato-12 and BARI Tomato-14 were graded as moderately resistant as the varieties showed 12.4 to 16.2% fruit infestation and revealed 1.0 to 1.3 larvae plant-1. The yield reduction and seed germination of these varieties ranged from 9.6 to13.2% and 66.7 to 73.3%, respectively. Only the variety BARI Tomato-7 was categorized as moderately susceptible which had significantly the highest abundance of fruit borer larva (1.7plant-1), fruit infestation (22.2%) and yield loss (15.9%), and lowest germination performance (62.7%). The study indicated that the varieties differed in their levels of resistance and this promising source of resistance may be incorporated in the integrated management of tomato fruit borer. SAARC J. Agri., 14(2): 150-161 (2016)